Menjelajahi Praktik Playdate di Indonesia: Tren Kegiatan Bermain dan Belajar untuk Anak Usia Dini di Playdate Familia Kreativa - Maryam Nibrosurrahman; Euis Kurniati; Mubiar Agustin (Institut Agama Islam Negeri Madura, 2025)
Play is a way for early childhood to learn. Currently, there are many play trends that are developing, one of them is playdate which is quite popular among urban parents. However, research related to the concept of playdate in Indonesia is still quite limited. Using the case study method, this research explores one of the playdate activities organized by playdate familia kreativa. The data collection techniques used are interviews, observation and documentation studies. The interview participants consisted of 3 familia kreativa playdate facilitators. The results of the study suggest that playdate familia kreativa is a community-based playdate that allows preschool children to carry out play activities while learning, as well as providing space for parents to be able to actualize themselves. Playdate Familia Kreativa also strives to bring back the fitrah of parents as the first place of education for their children, with a vision to become a reference for learning, working, and creating for families around the world with the principle of rahmatan lil'alamin.